2016
DOI: 10.1002/admi.201600313
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Vertically Aligned Carbon Nanotubes by a Novel Manganese Oxide Atomic Layer Deposition Process for Binder‐Free Hybrid Capacitors

Abstract: A novel atomic layer deposition process of manganese oxide from methylcyclopentadienyl manganese tricarbonyl and ozone has been developed. It is used to coat vertically aligned carbon nanotubes (VACNTs) grown on a conductive Inconel substrate in order to produce a 3D array of metal oxide-carbon nanotube electrode. Electron microscopy studies show that a conformal polycrystalline film can be deposited on the VACNTs arrays. X-ray diffraction, small area electron diffraction, and X-ray photoelectron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The reflections in the patterns of the composites situated at 8.3°, 13.2°, 14.7°, 16.4°, 26.6° and 28.5° correspond to the (101), (112), (103), (211), (224), (400) reflections of Mn 3 O 4 hausmannite (JCPDS Card No. 24‐734), respectively (some of them are weak and/or can be observed only in patterns recorded from thick samples deposited at high temperature) . The most intense reflections centered at 14.7° and 16.4° increase with the increasing of the deposition temperatures pointing to an increase of the crystallite size.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reflections in the patterns of the composites situated at 8.3°, 13.2°, 14.7°, 16.4°, 26.6° and 28.5° correspond to the (101), (112), (103), (211), (224), (400) reflections of Mn 3 O 4 hausmannite (JCPDS Card No. 24‐734), respectively (some of them are weak and/or can be observed only in patterns recorded from thick samples deposited at high temperature) . The most intense reflections centered at 14.7° and 16.4° increase with the increasing of the deposition temperatures pointing to an increase of the crystallite size.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, Mn 3 O 4 was deposited by ALD using MeCpMn(I)(CO) 3 and O 3 as precursors. It was shown that this new process could be applied in a large range of deposition temperatures (from 100 °C to 275 °C) . In general, the deposition temperature can significantly affect the materials deposited.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations